Loss to Follow-Up among HIV Positive Pregnant and Lactating Mothers on Lifelong Antiretroviral Therapy for PMTCT in Rural Uganda - Matilda Kweyamba; Esther Buregyeya; Joy Kusiima; Vianney Kweyamba; Aggrey David Mukose (Hindawi Limited, 2018)
Background. Mother-to-Child Transmission of HIV accounts for more than 90% of all pediatric HIV infections. However, Prevention of Mother-to-Child Transmission (PMTCT) of HIV through provision of lifelong ART to HIV positive mothers faces various challenges which affect its success. One of such challenges is the loss to follow-up (LTFU) of mothers. Methodology. We conducted a cross-sectional study utilizing both quantitative and qualitative data collection methods. We were able to trace 279 HIV positive, pregnant, and lactating mothers among mothers who were initiated on lifelong ART for PMTCT in public health facilities in Ntungamo district, Western Uganda. The proportion of those who were lost to follow-up was determined, and Log binomial regression with stepwise backward elimination method was employed to identify factors associated with LTFU. Focus group discussions (FDGs) of women on lifelong ART and key informant interviews (KIIs) of peer educators were also performed. Results. Out of the 279 mothers that were successfully traced and interviewed, 103 (37%) were identified as lost to follow-up. The prevalence of LTFU was higher among those whose transport costs were above $2.75, adj (adjusted) PR (Prevalence Ratio) 1.6 (95% CI; 1.02-2.55); those who waited beyond one hour before being attended to, adj PR 1.74 (95% CI; 1.02-2.96); and those who assumed that their infant was already infected, adj PR 1.76 (95% CI; 1.15-2.70). On interviews, LTFU in these mothers was attributed to fear of swallowing antiretroviral drugs, HIV related stigma and discrimination, inadequate facilitation of the peer educators, long patient waiting time, and transportation to the health facilities. Conclusion. More than one-third of mothers initiated on lifelong ART for PMTCT in Ntungamo district were lost to follow-up over a period of 25 months. Recommendations. Provision of regular and adequate pre-ART and ART adherence counseling and provision of routine health education would reduce LTFU.